Reduced device count multilevel inverter topology for renewable energy applications: a brief review - Hossain, Md Showkot; Hasan, Md Akib; Mohd Said, Nurul Ain; Abd Halim, Wahidah; Jidin, Auzani (2023)
Modern power converters are an essential component in the real-time deployment of renewable energy which makes the renewable energy harness more efficient. In medium power applications, multilevel inverters (MLI) seem to be a viable alternative to conventional inverters. This article attempts to provide a brief overview of new reduced device count multilevel inverter topologies focusing on renewable energy applications. This review article examines the most recent topologies into two categories which are single-source and multiple-source multilevel inverters. In recent times, researchers have tried to employ a small number of components in multilevel inverters in order to achieve low voltage stress and increased efficiency. Moreover, the overall comparison of these topologies is shown in a tabular representation. This comparison is based on the needed number of switches, number of de supplies, Number of capacitors & diodes, and the number of levels (NL) that are achieved by the multilevel inverter topologies. In addition to this, the equivalent THD of the output and efficiency arc taken into consideration.